PENGARUH TEKNIK SELF CONTROL TERHADAP PERILAKU KECANDUAN GAME ONLINE SISWA DI SMK MUHAMMADIYAH 2 PEKANBARU - Annisa, Usdiatul; Yakub, Elni; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of self control techniques on online game addiction behavior of students of Pekanbaru Muhammadiyah II Vocational School. This type of research is a quantitative research with Pre-Experiment method. The research design used in this study is "One Groups Pretest-Posttest Design". The measuring instrument used in this study is the scale of measurement of Online Game addiction behavior which consists of 50 items before being validated, and after the validity is obtained valid items amounting to 30 items with validity of 0,250 and reliability of 0.747. Determination of the subject using purposive sumpling technique, and getting 7 subjects from the Muhammadiyah 2 Pekanbaru Vocational High School who were identified as having a high level of online game addiction behavior. The data analysis technique used was a non-parametric statistical technique using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. For this reason, it can be concluded that there are differences in the scores of students' online game addiction behavior before and after being given treatment in the form of self control techniques. From the Rank Spream Test results obtained r = 0.782 while the correlation coefficient r2 is 0.612. Thus there is the effect of the Self Control technique on the online game addiction behavior of 0.61.2% students at the Muhammadiyah 2 Vocational School in Pekanbaru.Key Words: Self Control, Online Game Addiction Behavior for Vocational Students.